2011
DOI: 10.1051/0004-6361/201016360
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic dispersion in the Faber-Jackson relation for early-type galaxies as function of the mass and redshift

Abstract: Context. It has been reported that the intrinsic dispersion at constant magnitude in the structural relations of early-type galaxies is a useful tool to study the universality of these structural relations, that is to say, to study whether the structural relations depend on luminosity, wavelength, redshift, and/or environment. Aims. We study the intrinsic dispersion at approximately constant magnitude in the Faber-Jackson relation as a function of luminosity, mass, and redshift. Methods. We use a sample of app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…The huge difference in richness of the sub-samples mirrors the difficulty in measuring the velocity dispersion compared to surface brightness and half-light radii. Nevertheless, this bias is less of a problem in our analysis because our log(L) − log(σ) closely agrees with the one we would derive from the log(M) − log(σ) relationship of [33] obtained from a much richer sample of about 90,000 ETGs from the Sloan Digital Sky Survey (SDSS-DR7) spanning a magnitude range of 7 mag in both g and r filters. Their procedure requires either the mass derived from a mass-luminosity relation or the mass estimated from the VT.…”
Section: The Samplesupporting
confidence: 84%
See 1 more Smart Citation
“…The huge difference in richness of the sub-samples mirrors the difficulty in measuring the velocity dispersion compared to surface brightness and half-light radii. Nevertheless, this bias is less of a problem in our analysis because our log(L) − log(σ) closely agrees with the one we would derive from the log(M) − log(σ) relationship of [33] obtained from a much richer sample of about 90,000 ETGs from the Sloan Digital Sky Survey (SDSS-DR7) spanning a magnitude range of 7 mag in both g and r filters. Their procedure requires either the mass derived from a mass-luminosity relation or the mass estimated from the VT.…”
Section: The Samplesupporting
confidence: 84%
“…Only quite recently, the claim that a different slope exists for the FJ of bright and faint ETGs (∼4 for bright galaxies to ∼2.7 for faint objects) appeared in literature (see, e.g., [32], among others). Nigoche-Netro et al [33] confirmed the different slopes of the FJ relation in different magnitude ranges and suggested that its intrinsic dispersion depends on the history of galaxies, i.e., on the number and nature of transformations that have affected the galaxies along their lifetimes (collapse, accretion, interaction and merging).…”
Section: Introductionmentioning
confidence: 95%
“…Figure 5 shows that the SDSS M * σ relation exhibits clear evidence of a break in the power law 5 http://cosmo.nyu.edu/blanton/vagc/kcorrect.html (c.f. Nigoche-Netro et al 2011;Cappellari et al 2013;Cappellari 2016). We fit the data with…”
Section: The Relation Between Stellar Mass and Velocity Dispersionmentioning
confidence: 99%
“…We can better say that it is a sort of 2D version of the FP 1 . The deep analysis of Nigoche-Netro et al (2011) concluded that the scatter of the FJ depends on the history of galaxies, i.e. on the number and nature of the transformations that have affected the galaxies along their life times (collapse, accretion, interaction, and merging).…”
Section: The Faber-jackson Relationmentioning
confidence: 99%